An Ayurveda Management of Diabetic Peripheral Neuropathy: A Vibrotherm-Based Assessment of Treatment Efficacy (AYUSHDHARA, 2024)
Diabetic Neuropathy (DN) is a peripheral nerve disorder in individuals with diabetes, characterized by neuropathic pain, which can lead to severe complications if untreated. Conventional treatments often offer only short-term relief and carry side effects, prompting exploration of alternative therapies. A 59-year-old woman with poorly controlled type 2 diabetes, COPD, and low bone density presented with acute low back pain, radiating to the legs, and numbness in both palms and left leg. Despite allopathic treatment, her symptoms persisted, leading her to seek Ayurvedic care. Clinical examination revealed signs of diabetic peripheral neuropathy, osteopenia, and degenerative spine disease. Ayurvedic intervention focused on balancing Vata and Pitta doshas through therapies like Padabhyangam, Lepam, Dhanyamla dhara, Jambeerapinda swedam, Patrapota swedam, and Shastika pinda swedam, combined with internal medications such as Nishakatakadi kasayam, Pramehoushadi, Rasna Saptakam Kashayam, Kaisora Guggulu, Ksheerabala 101 cap, and Dhanwantharam Gritam. Assessment was conducted using Vibrotherm, Diabetic Neuropathy Examination (DNE), Michigan Neuropathy Screening Instrument (MNSI), and Toronto Clinical Neuropathy Score (TCNS). Post-treatment assessments showed significant improvement in symptoms, including reduced pain, numbness, and burning sensations. Objective measures using various neuropathy assessment tools indicated decreased neuropathy severity. The Ayurvedic treatment demonstrated efficacy in managing diabetic neuropathy symptoms, offering a viable alternative to conventional therapies. Early diagnosis and integrated Ayurvedic care can provide substantial symptom relief and improve the quality of life for diabetic neuropathy patients.